Perkin-Elmer atomic absorption spectrophotometer in use at National Institute for Occupational Safety and Health laboratory - Perkin-Elmer Corporation (1970)
General view of an unidentified chemist conducting an analysis using a Perkin-Elmer Model 403 Atomic Absorption Spectrophotometer in a laboratory associated with the National Institute for Occupational Safety and Health (NIOSH). Per notations accompanying the photograph, chemists working in NIOSH's Physical and Chemical Analysis Branch commonly used atomic absorption instruments to take precise measurements of potentially toxic trace metals in samples from workplaces and biological specimens.
Keywords: Atomic absorption spectroscopy; Employees; Perkin-Elmer Corporation; Scientific apparatus and instruments; Toxicity testing; Corporations; National Institute for Occupational Safety and Health; Laboratories